Research on automatic arrange and detect system for plentiful immethodical components. Issue 1 (March 2021) - Kui, Zhang; Ru, Zhang; Yaru, Cui; Hailong, Zhao; Huaguang, Liu; Honglei, Ran; Lijing, Yin
Abstract: With the development of electronic technology, the requirements for electronic components are gradually becoming chip, miniaturization and high precision. In this case, problems such as scattered sample parts and poor detection accuracy and stability in traditional production testing methods seriously affect production quality. Therefore, in-depth study of intelligent material discharge detection has become an important way to solve the problem. In this paper, the needs of intelligent detection are comprehensively analyzed, and the machine vision imaging optimization is deeply studied, feature matching and small sample capture placement technologies are learned. In order to realize intelligent discharge detection of micro scattered equipment, an automatic discharge system is developed, which integrates counting module, defect detection module and automatic discharge module.